Assessment of Demand Response Particibility Potential Based on Cost-Effective Process Design. Issue 3 (2021) - Liu, Yu; Campos, Gustavo; Palazoglu, Ahmet; El-Farra, Nael H.
Abstract: In this work, a model-based analytical framework is proposed to evaluate the cost-effectiveness of process design alternatives with respect to their ability to participate (particibility) in Demand Response (DR) services (such as load shifting under the Day-Ahead market) through the use of supply curves. The supply curves relate available DR capability to the investment cost of process design, and are constructed based on a specific DR service. Using the California Independent System Operator (CAISO) wholesale electricity market as a reference, the proposed framework is implemented to demonstrate the cost-benefits of considering DR aspects at the design stage. As a motivating example, the developed framework is illustrated using a CSTR-storage model, for which supply curves are generated under different scenarios. A visualization is provided of the effect of the process design capacities on the DR capability, as well as the limitations on the load-shifting capacity of a given process design.